Development and characterizations of polylactic acid (PLA) and polyglycolide acid (PGA) monofilaments for acupoint catgut embedding therapy applications. Issue 11 (2nd November 2019) - Fu, Shaoju; Yang, Dongchao; Zhang, Peihua
Abstract: Polylactic acid (PLA) and polyglycolide acid (PGA) are known for good biocompatibility. These features have resulted into significant academic and industrial research interest in various areas. However, in the acupoint catgut embedding therapy field, the existing PLA and PGA can't satisfy usage requirements due to their poor properties. This work designed novel melt-spinning system to produce different PLA and PGA monofilaments, and effects of spinning conditions on their comprehensive performances were characterized. The results showed that samples had the smooth surfaces and diameters decreased with spinning parameters. PLA-2 (Strength = 78.63 cN; Elongation = 57.28%) and PGA-2 (Strength = 57.34 cN; Elongation= 18.42%) perform the best mechanical properties. All the samples were non-toxicity, and PLA group degraded much slower than that of PGA group. In conclusion, this melt-spinning system showed potential in ACET application the optimum parameters ( v = 150 m/min, n = 6) were proved to have the higher prospect.